Evaluation of fieldwork practice in social work education at the University of Limpopo (Turfloop Campus) aligning theory and practice - Dimo, Peter Masibinyane (University of Limpopo (Turfloop Campus), 2013)
The study aimed at evaluating social work fieldwork practice at the University of Limpopo (Turfloop Campus) in relation to theory. The alignment of social work theory and practice is the goal of Social Work profession. Fieldwork practice in social work education forms the practical component of a social work curriculum. It is an essential bridge from classroom to service delivery settings as it provides an opportunity for social work students to connect theoretical education and fieldwork practice. However there is lack of integration between Social Work theory and Social Work fieldwork practice. There is indeed a continuing tension between theory and practice. With regard to the methodology, a combination of quantitative–qualitative research approach was used. Self-administered questionnaires, interview guide and focus group discussions were used to collect data from 3rd year and 4th year social work students as well as agency-based supervisors. The study revealed that social work fieldwork practice is essential for the integration of theory into practice. Therefore the department of Social Work at the University of Limpopo should organize workshops for agency-based supervisors to update their theoretical knowledge base. Fieldwork assessment tool should be reviewed and Social work students should also be involved in the assessment process and self-assessment should also be introduced.
Thesis (M.A. (Social Work)) --University of Limpopo, 2013
Keywords: Fieldwork practice; Social work fieldwork; 361.32; Social work education; Social sciences -- fieldwork